Profitability and investment: Evidence from India's organized manufacturing sector - Deepankar Basu; Debarshi Das (University of Massachusetts, Department of Economics, 2015)
Using a state-industry panel data set at the 3 digit national industrial classification (NIC) level of disaggregation for 19 major Indian states over the period 1983-84 to 2007-08, we analyze the contemporaneous and long run impacts of the rate of profit and its components - profit share, capacity utilization rate, and capacity-capital ratio - on investment. Our results show that: (a) the rate of profit has both short and long run positive impacts on investment; (b) the profit share and capacity-capital ratio have only long run positive impacts, and the capacity utilization rate has only a contemporaneous positive impact on investment.
Keywords: B51; E12; E22; 330; profitability; investment; manufacturing; India